Compliance of rural banks in the Ilocos provinces with the Bangko Sentral ng Pilipinas corporate governance regulations : basis for the development of a corporate governance model - Ranay, Frelyn B. (Laoag City : [s.n.], 2014)
This research paper determined the compliance of the Board of Directors of rural banks in the locos Provinces to the Bangko Sentral ng Pilipinas (BSP) corporate governance regulations as basis for formulating a corporate governance model for rural banks. The database survey covered thirteen rural banks in the locos Provinces, Philippines. Utilizing the Research and Development (R&D) methodology, the study made use of a questionnaire to gather data from the Board of Directors and bank managers of the rural banks in the locos provinces. The model was developed from the result of the study and rated as highly valid for adoption by experts in the banking industry. Generally, the result of the research study show that the Board of Directors' compliance to the Bangko Sentral ng Pilipinas (BSPs) corporate governance regulations can provide a valid ground for proposing a model for the rural banks which is of prime importance to the banking industry and development needs in the region and the country as a whole. Further, the rural banks in the locos provinces are governed by Boards of Directors who are educationally fit with long years of experience in arriving at decisions, formulating and implementing actions that ensure effective and accountable service. This enabled the rural banks to withstand the test of times. Presently, these banks are expanding and growing in terms of branches and employees, and sustaining their relevance in the banking industry and countryside by diversifying their services. Cultivating a culture of transparency and accountability, and imbibing a culture of sound corporate governance for the banks, in particular the rural banks as espoused by the BSP's Circular on Corporate governance were highly demonstrated by the Board of Directors of rural banks in the locos provinces.
Bibliography: pages 245-248.
CHED-La Union
Keywords: Banks and banking